Performance Analysis of the General and Protocol Section of the Regional Secretariat of North Toraja Regency - Ningrum, Eunike Karin; Yunus, Rabina; Irwan, Lukman (Newinera Publisher, 2025)
Employee performance plays a vital role in determining the success of an organization, particularly in government institutions where efficiency and effectiveness in public service delivery are crucial. This study analyzes the performance of employees in the General and Protocol Section of the North Toraja Regency Regional Secretariat based on six key indicators: quality, quantity, punctuality, effectiveness, independence, and work commitment. The research employs a qualitative descriptive approach, utilizing primary data from interviews and observations, as well as secondary data from relevant documents. Findings indicate that while employee performance is generally good, several areas require improvement, including the update of Standard Operating Procedures (SOP), asset management, and training participation. Furthermore, independence in task execution is still influenced by hierarchical decision-making, and financial realization has not fully met the targeted budget allocation. Strengthening work discipline, improving resource allocation, and enhancing communication and collaboration among employees are recommended to optimize performance outcomes.